2008
DOI: 10.1088/0953-2048/21/7/075009
|View full text |Cite
|
Sign up to set email alerts
|

Thermally and mechanically induced residual strain and strain tolerance of critical current in stainless steel-laminated Bi2223/Ag/Ag alloy composite superconductors

Abstract: It is known that the tensile strain tolerance of the critical current of Bi2223 composite superconductors is improved when the compressive residual strain of Bi2223 filaments in the current transport direction (sample length direction) is enhanced. In the present work, the thermally and mechanically induced residual strain accumulation process of a stainless steel-laminated Bi2223/Ag/Ag alloy superconducting composite tape fabricated at American Superconductor Corporation was studied. A calculation procedure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…3 compares the relationship between the stress and strain at 77 K, and that between the normalized critical current at the tively. These values correspond well with previously reported results where the fracture strain of the filament almost doubled owing to lamination [9][10][11]. In the next section, the maximum fatigue stress for SUS3ply tapes is selected according to the irreversible stress under the loading step, r l,irr95% , of 342 MPa, and that under the unloading step, r u,irr99% , of 315 MPa.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…3 compares the relationship between the stress and strain at 77 K, and that between the normalized critical current at the tively. These values correspond well with previously reported results where the fracture strain of the filament almost doubled owing to lamination [9][10][11]. In the next section, the maximum fatigue stress for SUS3ply tapes is selected according to the irreversible stress under the loading step, r l,irr95% , of 342 MPa, and that under the unloading step, r u,irr99% , of 315 MPa.…”
Section: Resultssupporting
confidence: 88%
“…It is also reported that the lamination suppresses the fracture of Bi2223 filaments. Consequently, the fracture strain of Bi2223 filaments in the laminated composite tapes is twice as much as that of filaments in the non-laminated composite tapes [9][10][11].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because the " r is negative (compressive) in the Bi2223 composite tape, as has been demonstrated by X ray diffraction analysis, 7,8) the actual fracture strain of the filaments in the composite tape is by À" r higher than the intrinsic fracture strain " f of the filaments alone. 2,4,[6][7][8]11,14) The " f À " r value is different from location to location within a specimen as well as from specimen to specimen. In the preceding works, 11,12) the heterogeneous damage behavior was formulated by the distributed " f À " r values and was correlated to the distribution of critical current values.…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Heterogeneous damage occurs, and the damage evolution behavior differs from specimen to specimen and from location to location within a specimen. [9][10][11][12][13][14] Accordingly, when a number of specimens are tested, the critical current differs from specimen to specimen.…”
Section: Introductionmentioning
confidence: 99%